Positive childhood experiences and adverse experiences: Psychometric properties of the Benevolent Childhood Experiences Scale (BCEs) among the Portuguese population - Almeida, Telma Catarina Ferreira de (2022)
Background: Positive childhood experiences have a positive effect on adulthood, and the absence of positive experiences can be more damaging throughout life than the presence of adversity. Recently, researchers have developed the Benevolent Childhood Experiences Scale (BCEs), an instrument designed to assess positive childhood experiences. Objectives: The present study aims to adapt the BCEs to the Portuguese population and examines its psychometric properties. Participants and settings: 1886 adults with a mean age of 36.36 years (SD = 13.66) from the community participated in this study. Methods: Participants responded to an online protocol consisting of a sociodemographic questionnaire, the BCEs, and the Childhood Trauma Questionnaire (CTQ). Results: Exploratory and confirmatory factor analysis revealed a one-factor structure for the BCEs with a good fit, CFI = 0.94; NFI = 0.92; RMSEA = 0.043 [0.036, 0.050]. Results also indicated satisfactory internal consistency and discriminant validity values. Predictive validity showed that higher BCEs scores predicted fewer adverse experiences in the last 3 years, but only before accounting for adverse childhood experiences. Conclusions: Overall, the results support the assertion that the Portuguese version of the BCEs is a valuable, brief, and psychometrically reliable instrument to measure positive childhood experiences that is suitable for use in Portugal.